1995
DOI: 10.1161/01.cir.92.10.2848
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Between Myocardial and Skeletal Muscle Injury by Assessment of the Plasma Ratio of Myoglobin Over Fatty Acid–Binding Protein

Abstract: The ratio of the concentrations of myoglobin over FABP in plasma from patients with muscle injury reflects the ratio found in the affected tissue. Since this ratio is different between heart (4.5) and skeletal muscle (20 to 70), its assessment in plasma allows the discrimination between myocardial and skeletal muscle injury in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
1
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(116 citation statements)
references
References 23 publications
1
107
1
6
Order By: Relevance
“…Moreover, in patients with acute myocardial infarction, it has been observed that the H type of FABP released from damaged or ischemic cardiac muscle appears in blood at the acute phase. 14 Recently, in comparison with the creatinine kinase MB-isoform or troponin-T, the blood concentration of H-type FABP was most sharply increased in patients visiting emergency departments for chest pain. Sandwich ELISA was found to be particularly useful for discovery of acute coronary syndrome within 6 h after its onset.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in patients with acute myocardial infarction, it has been observed that the H type of FABP released from damaged or ischemic cardiac muscle appears in blood at the acute phase. 14 Recently, in comparison with the creatinine kinase MB-isoform or troponin-T, the blood concentration of H-type FABP was most sharply increased in patients visiting emergency departments for chest pain. Sandwich ELISA was found to be particularly useful for discovery of acute coronary syndrome within 6 h after its onset.…”
Section: Discussionmentioning
confidence: 99%
“…Serum DNase I activity was significantly elevated within 3 hours of the onset of acute chest pain in the patients with AMI, whereas the serum levels of CK-MB and troponin T were slightly elevated and exceeded the cutoff levels in approximately 45% of those patients; we were thus able to detect the elevation of the serum DNase I activity earlier than that of CK-MB and troponin T. As an early marker for myocardial necrosis, the serum myoglobin level is a sensitive test but lacks cardiac specificity, because there may be an elevation in the serum levels of myoglobin secondary to musculoskeletal injury. 13 However, the serum DNase I activity level does not rise after trauma, and surgical trauma has been reported to induce no elevation of the activity, 14 suggesting that DNase I may be a more specific marker for AMI than myoglobin. Furthermore, there is a slight overlap between the levels of activity in patients with AMI and patients with OD (Figure, C).…”
Section: Discussionmentioning
confidence: 99%
“…H-FABP is produced mainly in the heart, but to a lesser extent, it is also produced in skeletal muscle (58 ). When patients suffered skeletal muscle injury as a result of cardioversion, multiorgan failure, postoperative states, or vigorous exercise such as running (59 ) or rowing (60 ), H-FABP was released into the blood.…”
Section: Clinical Interpretation Of Plasma H-fabp Concentrationsmentioning
confidence: 99%